Correction to: Probiotics' efficacy in paediatric diseases: which is the evidence? A critical review on behalf of the Italian Society of Pediatrics - Massimo Martinelli; Giuseppe Banderali; Marisa Bobbio; Elisa Civardi; Alberto Chiara; Sofia D'Elios; Andrea Lo Vecchio; Mattia Olivero; Diego Peroni; Claudio Romano; Mauro Stronati; Renato Turra; et al. (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.